Hepatoprotective role of Abelmoschus esculentus (Linn.) Moench., on carbon tetrachloride-induced liver injury. (September 2013) - Saravanan, Subramanian; Pandikumar, Perumal; Pazhanivel, Natesan; Paulraj, Michael Gabriel; Ignacimuthu, Savarimuthu
Abstract Context: Chronic liver disease has become a global health problem. The research for prominent herbal agents for the management of liver diseases is widely increased. Objective: The root of Abelmoschus esculentus (Linn.) Moench., (Malvaceae) has been used as a remedy for liver disorders. The aim of the present study was to evaluate the antioxidant and hepatoprotective effects of the ethanol extract of A. esculentus root. Materials and method: The antioxidant effect was assessed using DPPH and hydroxy radical scavenging assays. The hepatoprotective effect of the extract was evaluated using CCl4 intoxicated HepG2 cell line and Wistar rats by estimating the levels of hepatic and antioxidant markers. Results: The extract of A. esculentus showed IC50 values of 270.99 and 532.86 µg/mL for DPPH and hydroxy radical scavenging assays, respectively. The incubation of HepG2 cells with CCl4 drastically decreased the cell viability and increased the leakage of transaminases. Pre-treatment with the extract significantly restored the cell death by 31.25 and 39.04% at 200 and 400 µg/mL concentrations, respectively. The reduction of ALT leakage by the treatment was 18.62, 38.59 and 52.15% compared to the CCl4 treated cells at 100, 200 and 400 µg/mL, respectively. In in-vivo experiments also the treatment reduced the levels of transaminases, ALP, MDA, total bilirubin and hepatic TNFα levels as well as increased the antioxidant levels in a dose dependent manner. Histological observations of liver sections showed reduction in steatosis, necrosis and inflammation. Conclusion: The results substantiated the hepatoprotective activity of A. esculentus through its antioxidant capacity.